Fragments of autobiography: The concept of “flickering compassion” in Portraits of Women by Ksenija Atanasijević - Bašić Ivana (Glasnik Etnografskog Instituta SANU, 2020)
In our discussion we will explore how Ksenija Atanasijević, while writing about the poets and philosophers of ancient Greece, but also about Saint Teresa of Avila and George Sand, expressed her own understanding of the importance of women's scientific and artistic creativity, and also their emancipation. By choice of women she will write about, as well as emphasis on certain qualities of their personalities and their work, and the philosophical concepts she supported, Ksenija Atanasijević simultaneously created her implicit imaginary philosophical "I" in Portraits of Women. Therefore, the most precise genre definition of Portraits of Women would be fragments of flickering compassion towards the personalities she is describing, and compassion can be defined as a key characteristic of her entire oeuvre and life - empathy was the basis of Ksenija Atanasijevic's ethical philosophy and her social, pacifist and feminist engagement and at the same time it was in her opinion the most important value of human life. With this choice, Ksenija Atanasijević also anticipated the stance of contemporary feminism on the necessity of creating a female canon for shaping a women's personal and creative identity.